Preparation method of ce-mof electrospun fiber and application in photocatalytic elimination of biochemical toxic agent simulation agent

CN118007258BActive Publication Date: 2026-10-30FUZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410148018.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-02
Publication Date
2026-10-30
Estimated Expiration
2044-02-02

AI Technical Summary

Technical Problem

[0003]光催化技术在生物抗/抑菌抗病毒活性及化学毒剂消毒中展现良好的消除效果,但是传统半导体TiO2存在吸收谱窄、可见光下性能差等问题,难以适应在多种环境下对生化毒物毒素的快速、高效消除

Benefits of technology

本发明利用四(4-羧基苯基)卟啉(TCPP)、硝酸铈铵((NH4)2Ce(NO3)6)、9,10-二(4-羧基苯基)蒽(ADBA)或5,5-二氧-5H-二苯并[B,D]噻吩-3,7-二羧酸(BTDO)通过简易溶剂热反应合成稳定的三维配位连接的MOF。随后经静电纺丝工艺制备出具有强可见光吸收的Ce-MOF静电纺丝纤维。该静电纺丝纤维在模拟太阳光下对生物毒剂革兰氏阴性大肠杆菌的抗菌率达到99 %以上,且具有快速光催化降解化学毒剂芥子气模拟剂2-氯乙基乙基硫醚(2-CEES)的能力,可在45 min内将2-CEES光催化氧化为无毒亚砜化合物CEESO,降解率大于99%,且其经至少3个周期洗消循环后对2-CEES的降解率仍可保持大于99 %,是一种兼具抗菌和洗消脱毒的复合材料,在生化防护织物方面展现出巨大的应用潜力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118007258B_ABST
    Figure CN118007258B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of Ce-MOF electrostatic spinning fibers and application of the Ce-MOF electrostatic spinning fibers in photocatalytic elimination of biochemical toxic agent simulant, and is characterized in that: a stable three-dimensional coordination connected MOF is synthesized through simple solvothermal reaction of tetra(4-carboxyphenyl)porphyrin, cerium ammonium nitrate and a dicarboxylic acid compound, and then a Ce-MOF electrostatic spinning fiber with strong visible light absorption is prepared through an electrostatic spinning process. The electrostatic spinning fiber has an antibacterial rate of more than 99% on the biological toxic agent simulant gram-negative escherichia coli under visible light, and can photocatalytically oxidize chemical toxic agent mustard gas simulant CEES into non-toxic sulfoxide compound CEESO within 45 min, the degradation rate is greater than 99%, and at least 3 cycles of decontamination cycles can be maintained, so the composite material has antibacterial and decontamination detoxification functions, and has great application potential in biochemical protection fabrics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of composite fiber material products, specifically relating to a method for preparing Ce-MOF electrospun fibers and their application in photocatalytic antibacterial and mustard gas degradation. Background Technology

[0002] Sulfur mustard (HD) foaming agents were weaponized during World War I, causing severe and irreversible damage to the skin, eyes, and respiratory system of many soldiers. The threat of such chemical weapons still exists in parts of the world today. Detoxification of chemical warfare agents can be achieved through hydrolysis, dehydrohalogenation, or selective oxidation. Hydrolysis and dehydrohalogenation are generally slow reactions and difficult to completely degrade. A promising approach to detoxifying HD is the selective oxidation of the sulfide into the corresponding sulfoxides (HDO) and sulfones (HDO2). HDO is a substance virtually harmless to humans, while the fully oxidized product, HDO2, has similar toxicity to HD. Compared to other detoxification methods, this reaction has rapid reaction kinetics and fewer harmful byproducts.

[0003] Photocatalysis has demonstrated excellent elimination effects in biological antibacterial / antiviral activities and chemical disinfection. However, traditional semiconductor TiO2 suffers from narrow absorption spectra and poor performance under visible light, making it difficult to adapt to the rapid and efficient elimination of biochemical toxins in various environments. Metal-organic frameworks (MOFs), as a class of crystalline porous materials constructed from metal ions / clusters and organic linkers, possess atomically precise and customizable structures and unique physicochemical properties, bridging the gap between heterogeneous and homogeneous catalysts. Over the past decade, MOFs have been used as adsorbents and catalysts to remove toxic chemicals from the air. MOFs can be modified by altering linkers, pore size, functional groups, and substituting metal nodes. This vast diversity means it is possible to design materials to capture and degrade specific target molecules. Furthermore, the high specific surface area, high porosity, and high crystallinity of MOFs allow them to expose or contact catalytically active sites, facilitating the effective adsorption and degradation of mustard gas. The structural versatility of MOFs also provides flexible construction methods, extending light sensitivity across a wide spectral range. MOF composite materials are an important component of future wearable self-degradable protective equipment such as protective clothing. Summary of the Invention

[0004] The purpose of this invention is to provide a method for preparing Ce-MOF electrospun fibers. These electrospun fibers have strong visible light absorption properties and can effectively kill and degrade Gram-negative Escherichia coli and mustard gas mimic 2-chloroethyl ethyl sulfide (CEES) under visible light. They also have good decontamination cycle performance and have good application prospects in photocatalytic elimination of biochemical agents.

[0005] To achieve the above objectives, the present invention adopts the following technical solution: A Ce-MOF electrospun fiber, the preparation method of which includes the following steps: 1) Mix cerium ammonium nitrate ((NH4)2Ce(NO3)6), tetrakis(4-carboxyphenyl)porphyrin (TCPP) with a dicarboxylic acid compound, then add a mixture of N,N-dimethylformamide and deionized water or ethanol, and add a regulator. After thorough dispersion by ultrasound, seal the mixture and react at 120 °C for 3 days. 2) Centrifuge the reaction solution obtained in step 1) to collect the solid, wash it three times with N,N-dimethylformamide and anhydrous ethanol respectively, and then dry it under vacuum at 60 °C to obtain MOF powder; 3) Add the MOF powder and polyacrylonitrile powder obtained in step 2) together to N,N-dimethylformamide, stir thoroughly to prepare a spinning solution, and then perform electrospinning on the obtained spinning solution. 4) Dry the fiber membrane obtained by electrospinning in step 3) at 60 °C to obtain the Ce-MOF electrospun fiber.

[0006] Furthermore, the mass ratio of cerium ammonium nitrate, tetra(4-carboxyphenyl)porphyrin and dicarboxylic acid compound used in step 1) is 159:20:(0-50).

[0007] Further, the dicarboxylic acid compound mentioned in step 1) is 9,10-bis(4-carboxyphenyl)anthracene (ADBA) or 5,5-dioxo-5H-dibenzo[B,D]thiophene-3,7-dicarboxylic acid (BTDO).

[0008] Further, in step 1), the volume ratio of N,N-dimethylformamide to deionized water or ethanol in the mixture is 3:1.

[0009] Furthermore, the regulator used in step 1) is glacial acetic acid (HAc). Trifluoroacetic acid (TFA) can also be used when cultivating single crystals, but its amount shall not exceed half the volume of the added mixture.

[0010] Furthermore, the mass ratio of MOF powder to polyacrylonitrile powder used in step 3) is 1:4 to 2:3.

[0011] Furthermore, the MOF powder used in step 3) needs to be pre-ground.

[0012] Furthermore, the process parameters for electrospinning in step 3) are: negative voltage -1.5 kV, positive voltage 8.5 kV, feed speed of 0.06 mm / min, and needle distance of 15 cm from receiving device.

[0013] The resulting Ce-MOF electrospun fibers can be made into protective clothing or protective masks for photocatalytic elimination of biological agents such as Gram-negative Escherichia coli and chemical agents such as mustard gas.

[0014] The beneficial effects of this invention are as follows: This invention utilizes tetrate(4-carboxyphenyl)porphyrin (TCPP), cerium ammonium nitrate ((NH4)2Ce(NO3)6), 9,10-bis(4-carboxyphenyl)anthracene (ADBA), or 5,5-dioxo-5H-dibenzo[B,D]thiophene-3,7-dicarboxylic acid (BTDO) to synthesize stable three-dimensionally coordinated MOFs via a simple solvothermal reaction. Subsequently, Ce-MOF electrospun fibers with strong visible light absorption are prepared using an electrospinning process. This electrospun fiber exhibits an antibacterial rate of over 99% against Gram-negative Escherichia coli under simulated sunlight. It also possesses the ability to rapidly photocatalytically degrade the chemical agent mustard gas mimic 2-chloroethyl ethyl sulfide (2-CEES). Within 45 minutes, it can photocatalytically oxidize 2-CEES into the non-toxic sulfoxide compound CEESO with a degradation rate greater than 99%. Even after at least three decontamination cycles, the degradation rate of 2-CEES remains greater than 99%. This composite material combines antibacterial and decontamination properties, demonstrating significant application potential in biochemical protective fabrics. Attached Figure Description

[0015] Figure 1 The XRD diffraction patterns are those of the MOF powders prepared in Examples 1 and 3.

[0016] Figure 2 The image shows the XRD diffraction patterns of MOF powders prepared with different amounts of glacial acetic acid in Example 2.

[0017] Figure 3 Fourier transform infrared spectra of Ce-TCPP prepared in Example 1 and Ce-TCPP-ADBA(2.0) prepared in Example 2.

[0018] Figure 4 The UV-Vis spectra of Ce-TCPP prepared in Example 1 and Ce-TCPP-ADBA(2.0) prepared in Example 2 are shown.

[0019] Figure 5A morphological comparison of pure polyacrylonitrile fiber material (left) and Ce-TCPP prepared in Example 1 (right).

[0020] Figure 6 Scanning electron microscope images of pure polyacrylonitrile fiber material (left) and Ce-TCPP prepared in Example 1 (right).

[0021] Figure 7 This is a comparison chart showing the activity of different electrospun fibers prepared in Examples 1 and 3 in degrading mustard gas simulants.

[0022] Figure 8 This is a comparison chart showing the activity of the mustard gas simulant for electrospun fibers prepared with different amounts of glacial acetic acid in Example 2.

[0023] Figure 9 The graph shows the cyclic performance test results of Ce-TCPP-ADBA(2.0) in Example 2 for degrading mustard gas simulant. Detailed Implementation

[0024] A Ce-MOF electrospun fiber, the preparation method of which includes the following steps: 1) Add 159 mg of cerium ammonium nitrate ((NH4)2Ce(NO3)6), 20 mg of tetrakis(4-carboxyphenyl)porphyrin (TCPP), and 0-50 mg of 9,10-bis(4-carboxyphenyl)anthracene (ADBA) or 5,5-dioxo-5H-dibenzo[B,D]thiophene-3,7-dicarboxylic acid (BTDO) to a 15 mL quartz glass bottle. Then add a mixture of 7.5 mL of N,N-dimethylformamide and 2.5 mL of deionized water (or ethanol), and add 0.5 mL to 4.0 mL of glacial acetic acid. After thorough ultrasonic dispersion, seal the bottle and transfer it to a 120 ℃ oven for reaction for 3 days. 2) Centrifuge the reaction solution obtained in step 1) to collect the solid, wash it three times with N,N-dimethylformamide and anhydrous ethanol respectively, and then dry it under vacuum at 60 °C to obtain MOF powder; 3) After grinding the MOF powder obtained in step 2), weigh 20 mg and add it together with 80 mg of polyacrylonitrile powder and 1 mL of N,N-dimethylformamide into a container and stir thoroughly to prepare a spinning solution. Then transfer the spinning solution to an electrospinning device and set the process parameters as follows: negative voltage of -1.5 kV, positive voltage of 8.5 kV, feed speed of 0.06 mm / min, and needle distance of 15 cm from the receiving device for electrospinning. 4) The fiber material obtained by electrospinning in step 3) is dried in a vacuum drying oven at 60 ℃ to obtain Ce-MOF electrospun fiber.

[0025] To make the content of this invention easier to understand, the technical solution of this invention will be further described below with reference to specific embodiments, but this invention is not limited thereto.

[0026] Example 1: Preparation of Ce-TCPP 1) Add 159 mg of cerium ammonium nitrate and 20 mg of tetrakis(4-carboxyphenyl)porphyrin to a 15 mL quartz glass bottle, then add a mixture of 7.5 mL of N,N-dimethylformamide and 2.5 mL of deionized water, and add 2.0 mL of glacial acetic acid. After thorough ultrasonic dispersion, seal the bottle and transfer it to a 120 ℃ oven for reaction for 3 days. 2) The obtained reaction solution was centrifuged to collect the solid, and washed three times with N,N-dimethylformamide and anhydrous ethanol respectively. After drying under vacuum at 60 °C, MOF powder was obtained. 3) After grinding the obtained MOF powder, weigh 20 mg and place it together with 80 mg of polyacrylonitrile powder and 1 mL of N,N-dimethylformamide in a container and stir thoroughly to prepare a spinning solution. Then transfer the spinning solution to an electrospinning device and set the negative voltage to -1.5 kV, the positive voltage to 8.5 kV, the feed speed to 0.06 mm / min, and the needle distance to the receiving device to 15 cm for electrospinning. 4) The fiber material obtained by electrospinning is dried in a vacuum drying oven at 60 ℃ to obtain Ce-TCPP electrospun fiber.

[0027] Example 2: Preparation of Ce-TCPP-ADBA 1) Add 159 mg of cerium ammonium nitrate, 20 mg of tetrakis(4-carboxyphenyl)porphyrin and 50 mg of 9,10-di(4-carboxyphenyl)anthracene to a 15 mL quartz glass bottle, then add a mixture of 7.5 mL of N,N-dimethylformamide and 2.5 mL of deionized water, and add 0.5 mL, 1.0 mL, 2.0 mL and 4.0 mL of glacial acetic acid respectively. After thorough dispersion by ultrasonication, seal and transfer to an oven at 120 °C for reaction for 3 days. 2) The obtained reaction solution was centrifuged to collect the solid, and washed three times with N,N-dimethylformamide and anhydrous ethanol respectively. After drying under vacuum at 60 °C, MOF(x) powder was obtained, where x = 0.5, 1.0, 2.0, and 4.0. 3) After grinding the obtained MOF powder, weigh 20 mg and place it together with 80 mg of polyacrylonitrile powder and 1 mL of N,N-dimethylformamide in a container and stir thoroughly to prepare a spinning solution. Then transfer the spinning solution to an electrospinning device and set the negative voltage to -1.5 kV, the positive voltage to 8.5 kV, the feed speed to 0.06 mm / min, and the needle distance to the receiving device to 15 cm for electrospinning. 4) The fiber material obtained by electrospinning is dried in a vacuum drying oven at 60 ℃ to obtain Ce-TCPP-ADBA(x) electrospun fiber, where x=0.5, 1.0, 2.0, 4.0.

[0028] Example 3: Preparation of Ce-TCPP-BTDO 1) Add 159 mg of cerium ammonium nitrate, 20 mg of tetrakis(4-carboxyphenyl)porphyrin and 30 mg of 5,5-dioxo-5H-dibenzo[B,D]thiophene-3,7-dicarboxylic acid to a 15 mL quartz glass bottle, then add a mixture of 7.5 mL of N,N-dimethylformamide and 2.5 mL of deionized water, and add 2.0 mL of glacial acetic acid. After thorough ultrasonic dispersion, seal the bottle and transfer it to a 120℃ oven for reaction for 3 days. 2) The obtained reaction solution was centrifuged to collect the solid, and washed three times with N,N-dimethylformamide and anhydrous ethanol respectively. After drying under vacuum at 60 °C, MOF powder was obtained. 3) After grinding the obtained MOF powder, weigh 20 mg and place it together with 80 mg of polyacrylonitrile powder and 1 mL of N,N-dimethylformamide in a container and stir thoroughly to prepare a spinning solution. Then transfer the spinning solution to an electrospinning device and set the negative voltage to -1.5 kV, the positive voltage to 8.5 kV, the feed speed to 0.06 mm / min, and the needle distance to the receiving device to 15 cm for electrospinning. 4) The fiber material obtained by electrospinning is dried in a vacuum drying oven at 60 ℃ to obtain Ce-TCPP-BTDO electrospun fiber.

[0029] Application Example 1: Antibacterial Test of Ce-MOF Electrospun Fibers After resuscitation and passage (third-generation strain), a certain amount of *E. coli* was placed in nutrient agar medium and incubated at 37 °C for 18 h. The OD value of the corresponding strain was measured using a microplate reader. Then, 1 mL of bacterial solution was placed in a glass test tube containing 9 mL of culture medium and diluted 10-fold to obtain a suitable concentration. Ce-MOF electrospun fibers prepared in the example were cut to a suitable size and placed at the bottom of a 12-well plate. 1.5 mL of the diluted bacterial solution was added to each well of the 12-well plate. The plates were illuminated with xenon lamps for 0 min, 10 min, 20 min, 30 min, 40 min, and 50 min. 100 μL of the bacterial solution was then taken from each well and spread onto a solid culture medium. Tests under dark and blank conditions served as control groups. All plates were incubated at 37 °C for 12 h and photographed.

[0030] The results showed that the antibacterial rate against Gram-negative Escherichia coli in each experimental group with Ce-MOF electrospun fibers reached over 99% after 50 minutes of simulated sunlight exposure.

[0031] Application Example 2: Ce-MOF electrospun fiber degradation mustard gas simulant test After adding 200 mL of deionized water and 20 μL of mustard gas simulant (2-CEES) to the reactor, the mixture was stirred evenly on a magnetic stirrer. Then, the Ce-MOF electrospun fibers prepared in the previous example were cut into small pieces and impregnated in the reactor, followed by ultrasonic treatment for 10 minutes. The reactor was then stirred again on a magnetic stirrer to reach adsorption equilibrium. After one hour, a xenon lamp was placed to directly irradiate the reactor with the light wavelength set to the full wavelength range. Samples were taken at regular intervals, 2.5 mL each time. After filtration through an organic filter, 2 mL of the filtered solution was added to 3 mL of chromatographically pure dichloromethane and shaken to mix thoroughly. The mixture was then allowed to stand, and after separation, the lower layer was collected using a syringe. The remaining product was detected using high-performance liquid chromatography (HPLC).

[0032] like Figure 7 , 8 As shown, all Ce-MOF electrospun fibers of the present invention can convert 99% of 2-CEES into CEESO within 45 min. Among them, Ce-TCPP-ADBA(2.0) has the shortest degradation time, which is 30 min; Ce-TCPP-BTDO has a longer degradation time, which is 45 min.

[0033] Application Example 3: Degradation Performance Test of Ce-MOF Composite Fiber Material under 2-CEES Cyclic Determination After using Ce-TCPP-ADBA(2.0) in Application Example 2, the undegraded 2-CEES and degradation product CEESO were washed with deionized water and ethanol respectively to remove them. The product was then dried in an oven and the experiment was repeated twice (30 min each time) according to the method of Application Example 2.

[0034] like Figure 9 As shown, the degradation rate of 2-CEES by Ce-TCPP-ADBA(2.0) after three cycles of cyclic washing and disinfection is still greater than 99%.

[0035] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made within the scope of the claims of the present invention should be included in the scope of the present invention.

Claims

1. A method for preparing Ce-MOF electrospun fibers, characterized in that, Includes the following steps: 1) Mix cerium ammonium nitrate, tetrakis(4-carboxyphenyl)porphyrin and dicarboxylic acid compound, then add N,N-dimethylformamide and a mixture of deionized water or ethanol, and add a regulator. After thorough dispersion by ultrasound, seal and react at 120 °C for 3 days. 2) Centrifuge the reaction solution obtained in step 1) to collect the solid, wash it three times with N,N-dimethylformamide and anhydrous ethanol respectively, and then dry it under vacuum at 60 °C to obtain MOF powder; 3) Add the MOF powder and polyacrylonitrile powder obtained in step 2) together to N,N-dimethylformamide, stir thoroughly to prepare a spinning solution, and then perform electrospinning on the obtained spinning solution. 4) Dry the fiber membrane obtained by electrospinning in step 3) at 60 °C to obtain the Ce-MOF electrospun fiber; The dicarboxylic acid compound mentioned in step 1) is 9,10-bis(4-carboxyphenyl)anthracene or 5,5-dioxo-5H-dibenzo[B,D]thiophene-3,7-dicarboxylic acid.

2. The method for preparing Ce-MOF electrospun fibers according to claim 1, characterized in that, The mass ratio of cerium ammonium nitrate, tetra(4-carboxyphenyl)porphyrin and dicarboxylic acid compound used in step 1) is 159:20:(0-50).

3. The method for preparing Ce-MOF electrospun fibers according to claim 1, characterized in that, In step 1), the volume ratio of N,N-dimethylformamide to deionized water or ethanol in the mixture is 3:

1.

4. The method for preparing Ce-MOF electrospun fibers according to claim 1, characterized in that, The regulator used in step 1) is glacial acetic acid or trifluoroacetic acid, and its amount shall not exceed half the volume of the added mixture.

5. The method for preparing Ce-MOF electrospun fibers according to claim 1, characterized in that, The mass ratio of MOF powder to polyacrylonitrile powder used in step 3) is 1:4 to 2:

3.

6. A Ce-MOF electrospun fiber prepared by the method according to any one of claims 1-5.

7. The application of Ce-MOF electrospun fiber as described in claim 6 in photocatalytic elimination of biochemical agents.

8. The application according to claim 7, characterized in that, The biochemical agents include the biological agent Gram-negative Escherichia coli and the chemical agent mustard gas.

9. The application according to claim 7, characterized in that, Its application method is to use the Ce-MOF electrospun fibers to prepare protective clothing or protective masks.

Citation Information

Patent Citations

  • Method for preparing PAN / POMs composite fiber membrane through electrostatic spinning

    CN104947226A

  • Electrostatic spinning membrane with adsorptive catalysis function and preparation method and application thereof

    CN108385274A